Face-validation of quality indicators for the organization of palliative care in hospitals in Indonesia: a contribution to quality improvement. - Effendy, Christantie; Vissers, Kris; Woitha, Kathrin; van Riet Paap, Jasper; Tejawinata, Sunaryadi; Vernooij-Dassen, Myrra; Engels, Yvonne (Supportive Care in Cancer, 2014)
Purpose: Quality indicators (QIs) for the organization of palliative care (PC) can contribute to quality improvement as they assess the key elements for adequate organization of care. They might differ between health care organization, cultures and economic resources. The aim of this study was face-validate an Indonesian set of QIs based on a European set, to compare the two sets of QIs and to test the applicability of Indonesian set.Methods: A modified two-round RAND Delphi process was conducted in Indonesia. Twenty-four health care professionals from different disciplines were invited as panellists to rate clarity and usefulness of 98 QIs. Next, a applicability pilot test took place in five hospitals.Results: A total of 21 panellists considered 76 QIs (78 %) face-valid and added two new ones. Of the QIs with the highest ratings, eight were evaluated by head nurses and two by reviewing 50 patient records. Each QI was met by at least two hospitals, and only one by all five. Regarding the two QIs on structured clinical record keeping, most medical records contained multidimensional aspects of care.Conclusions: We found that most QIs for the organization of PC developed for European countries were also considered face-valid for Indonesian hospitals. The top 10 QIs were applicable in Indonesia. This suggests that most of the organizational QIs are universal rather than country specific. The Indonesian set of QIs should be considered as a first step in developing, testing, and implementing a set of QIs for PC in Indonesia. We recommend validation in other Asian regions.